تعلیم علم البیانات بأقسام ومدارس المکتبات والمعلومات بالجامعات الأمریکیة : دراسة تحلیلیة - د. مشیرة أحمد صالح (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims to identify the concept of data science and big data, as itaims to identify the characteristics of the courses of data science in a sample ofthe departments and schools of libraries and information in American universitiesduring the academic year 2019/2020, using the descriptive analytical approach.The study reached several results, including: 213 special data science coursesare available, representing 13.6% of the total courses available in the library andinformation schools. The study concluded with several recommendations, themost prominent of which is reconsidering the objectives and contents of thecurrent programs of the libraries and information departments, and working toalign them with the requirements of the labor market, especially in the field ofdata science .